2014
DOI: 10.1016/j.cell.2014.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Programmed –1 Frameshifting by Kinetic Partitioning during Impeded Translocation

Abstract: Programmed -1 ribosomal frameshifting (-1PRF) is an mRNA recoding event utilized by cells to enhance the information content of the genome and to regulate gene expression. The mechanism of -1PRF and its timing during translation elongation are unclear. Here, we identified the steps that govern -1PRF by following the stepwise movement of the ribosome through the frameshifting site of a model mRNA derived from the IBV 1a/1b gene in a reconstituted in vitro translation system from Escherichia coli. Frameshifting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
288
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(315 citation statements)
references
References 55 publications
27
288
0
Order By: Relevance
“…Previous work has shown that −1 frameshifting occurs during translocation, and is the result of uncoupling of translocation and back-rotation of the small subunit, resulting in an unusual rotated state (Caliskan et al, 2014; Chen et al, 2014). Thus, our data strongly suggest that the Fap7-regulated release of Dim1 is a functional test for correct adoption of the rotated state by nascent 40S subunits and further emphasize the importance of quality control during ribosome assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that −1 frameshifting occurs during translocation, and is the result of uncoupling of translocation and back-rotation of the small subunit, resulting in an unusual rotated state (Caliskan et al, 2014; Chen et al, 2014). Thus, our data strongly suggest that the Fap7-regulated release of Dim1 is a functional test for correct adoption of the rotated state by nascent 40S subunits and further emphasize the importance of quality control during ribosome assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Careful kinetic and thermodynamic measurements have demonstrated a near-equilibrium for the different ribosome conformations (Munro et al, 2009). Interestingly, programmed frameshifting occurs by manipulation of the translocation process (Caliskan et al, 2014; Chen et al, 2014). Both of these observations underscore the importance and delicacy of this process.…”
Section: (Introduction)mentioning
confidence: 99%
“…SD motifs have well-characterized roles in frameshifting in bacteria: in the dnaX gene, an internal SD motif contributes to −1 frameshifting at a slippery sequence followed by an mRNA hairpin (Larsen et al, 1994). In vitro studies on this system have shown that the downstream hairpin blocks translocation (Caliskan et al, 2014; Chen et al, 2014), resulting in a kinetic pause; this in turn allows different codons and reading frames to be sampled on the slippery sequence (Caliskan et al, 2015; Yan et al, 2015). In the metastable state where the ribosome slips on the message, the SD motif stabilizes the interaction with the mRNA in a new position.…”
Section: Discussionmentioning
confidence: 99%
“…Among indirect translocation assays, the tandem LC/MS/MS analysis of oligopeptide composition deduces the ribosome reading frame based on the synthesized peptide [8]. Fluorescently labeled tRNA binding/moving events reveal the translating codons [9], and the puromycin reactivity assay is the conventional method for confirming the A-site vacancy resulting from translocation [10]. None of these methods can reveal the movement at the 5ʹ end of the mRNA that is entering the ribosome.…”
Section: Introductionmentioning
confidence: 99%